COVID-19 DISEASE 2019: A REVIEW ARTICLE - Salil, Salil Sanghvi; Mangal S. Panwar (Journal of Global Pharma Technology, 2025)
Corona viruses are a group of enveloped viruses with no segmented, single-stranded, and positive-sense RNA genomes. Corona viruses belong to the “Coronaviridae family”, which causes various diseases, from the common cold to SARS and MERS. In March 2020 the World Health Organization declared the SARS-Cov-2 virus a global pandemic. We performed a review to describe existing literature about Corona Virus Disease 2019 (COVID-19) history, Symptoms, Epidemiology, Clinical features, Clinical manifestations, Diagnosis, Treatment, Prevention. Keywords: COVID-19, Symptoms, Epidemiology, Clinical features, Clinical manifestations, Diagnosis, Treatment, Prevention.